Perencanaan Bangunan Instalasi Pengolahan Air Limbah Komunal Industri Tahu di Kabupaten Jombang - Aisyah Nadia; Okik Hendriyanto Cahyonugroho (Jurnal Serambi Engineering, 2024)
Tofu is a food product made from soya beans and is a widely used cottage industry in Jombang district. Many people engage in this business because the production process is relatively simple and does not require complicated equipment. Tofu is also a product with fairly stable demand in local and regional markets, making it an attractive business option for small and medium enterprises (MSMEs). Due to cost constraints, some industries do not have wastewater treatment. Waste from production is discharged directly into watercourses, leading to degradation of the surrounding environment. This research aims to design the wastewater treatment plant (WWTP) in Jombang. A total of 600 m3 / day of wastewater is discharged from 70 tofu industries. Based on the wastewater discharge, a water treatment system is planned in the form of an equalisation tank (27.386 x 9.1287 x 2 m), settling tank (32.533 x 38.73 x 2 m), anaerobic baffle reactor with a total of 6 compartments (103.28 x 38.7 x 2 m), aeration (37.879 x 11 x 1.8 m), and finally wetland (103.36 x 38.7 x 2 m). The area required is 5926.667 m2.